Moral hazard in producer organizations - some experiences of an empirical survey - Kovács , Zoltán (Applied Studies in Agribusiness and Commerce, 2016)
A wide range of empirical experiences shows that the performance of Hungarian producer organizations (aka TÉSZ) significantly falls behind the activity observed in the developed Western European countries. Regarding this issue, the present study examines how moral hazard - as one of the possible reasons - influences the producers’ activities in cooperative organizations. Information for the research was collected with the help of a questionnaire survey among the members of PaprikaKert TÉSZ Ltd. A statistical path model has been developed for the research, which assumed that - in addition to a direct effect - moral hazard also affects collaborative activity by eroding trust. The statistical model has been tested both in member-member and members-management relations. The experiences from the survey clearly show that moral hazard exists in the producer organization. According to my results, though its measure cannot be regarded numerically considerable, its negative effect on cooperative activity can be proved with statistical examinations. Its effect can be divided into two aspects: besides a direct effect, an indirect one can also be detected, which means that moral hazard is able to reduce producers’ willingness to cooperate by eroding trust. Moreover, our results have clearly pointed out that moral hazard has a negative impact on member-member and members-management relations to varying degrees and through different mechanisms. In addition to the above tests, the empirical testing of another model called Sholtes trust model has been carried out, too. The validating was successful, so the model - which attributes trust to the faith in the partner’s loyalty and capability - is basically acceptable. The argument says that high-level trust can be observed among partners only when faith both in loyalty and capability is strong enough. The research, however, revealed that the above-mentioned two factors determine it in a different way: regarding trust between members, the faith in capability is more important; while trust towards the management is more determined by faith in loyalty.JEL code: Q12, Q13